2018
DOI: 10.3164/jcbn.17-101
|View full text |Cite
|
Sign up to set email alerts
|

Habitual exercise decreases plasma xanthine oxidoreductase activity in middle-aged and older women

Abstract: The aim of present study was to investigate the association between plasma xanthine oxidoreductase activity, which has gained attention as a novel preventive target of cardiovascular disease, and various physiological parameters and was to determine the effects of habitual exercise on plasma xanthine oxidoreductase activity in middle-aged and older women. In the cross-sectional study, we investigated the association between plasma xanthine oxidoreductase activity and various physiological parameters in 94 midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…(19) Our previous study also demonstrated that plasma XOR activity was significantly correlated with BMI, visceral fat area, waist circumference, systolic blood pressure, fasting glucose, and daily step counts in middle-aged and older women. (25) In addition to these findings, the present observations confirmed that plasma XOR activity was significantly correlated with handgrip strength, serum 8-OHdG, and the clustered CMR score in overweight and obese men. To the best of our knowledge, this pilot study provides one of the first pieces of evidence that plasma XOR activity can be associated with muscular strength, oxidative stress, and clustered CMR in overweight/obesity.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…(19) Our previous study also demonstrated that plasma XOR activity was significantly correlated with BMI, visceral fat area, waist circumference, systolic blood pressure, fasting glucose, and daily step counts in middle-aged and older women. (25) In addition to these findings, the present observations confirmed that plasma XOR activity was significantly correlated with handgrip strength, serum 8-OHdG, and the clustered CMR score in overweight and obese men. To the best of our knowledge, this pilot study provides one of the first pieces of evidence that plasma XOR activity can be associated with muscular strength, oxidative stress, and clustered CMR in overweight/obesity.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have reported that plasma XOR activity assessed using the same assay in our study was correlated with BMI, waist circumference, blood pressure, smoking, alanine aminotransferase, uric acid, HDL cholesterol, triglycerides, hemoglobin A1c, fasting glucose and insulin, HOMA-IR, and several adipokines in the Japanese general population.‍ ( 21 , 22 ) Similarly, another previous study in a small number of young adults showed that plasma XOR activity was positively correlated with BMI, uric acid, high-sensitivity C-reactive protein, and negatively correlated with the quantitative insulin sensitivity check index and adiponectin.‍ ( 19 ) Our previous study also demonstrated that plasma XOR activity was significantly correlated with BMI, visceral fat area, waist circumference, systolic blood pressure, fasting glucose, and daily step counts in middle-aged and older women.‍ ( 25 ) In addition to these findings, the present observations confirmed that plasma XOR activity was significantly correlated with handgrip strength, serum 8-OHdG, and the clustered CMR score in overweight and obese men. To the best of our knowledge, this pilot study provides one of the first pieces of evidence that plasma XOR activity can be associated with muscular strength, oxidative stress, and clustered CMR in overweight/obesity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…First is the cross-sectional design, thus even though relationships were explored in predictive terms, the results cannot be interpreted to show causal relationships. Second, while physical activity has been shown to influence XOR activity ( 51 53 ), no survey of physical activity was conducted in the present study. Furthermore, we were unable to fully investigate the association of dosage, duration, or indication of XOR inhibitor administration with sarcopenia.…”
Section: Discussionmentioning
confidence: 85%
“…Using this method, we and others have recently demonstrated that plasma XOR activity is a new biomarker of metabolic disorders associated with obesity, insulin resistance, liver dysfunction, hyperuricemia and adipokines [6][7][8][9]. In addition, it has been reported that habitual exercise can decrease plasma XOR activity [10]. However, little is known about predictors for change in plasma XOR activity in a longitudinal course.…”
mentioning
confidence: 99%